The Urgency of Stakeholder Roles and Environmental Politics in Achieving SDGs through Environmental Management in Malaumkarta Village, Sorong - Sinaga, Melpayanty; Suryanti, Made Selly Dwi (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study examines the implementation of Sustainable Development Goals (SDGs) through the traditional egek/sasi practices in Malaumkarta Village, Sorong Regency, Indonesia. It explores the roles of various stakeholders in integrating indigenous ecological knowledge with modern conservation efforts to achieve sustainable development. Using a qualitative case study approach, it highlights the role of a multi-stakeholder collaboration, including local youth, NGOs, religious institutions, local government, and the customary council. The study reveals that the successful localization of SDGs in Malaumkarta is attributed to a robust multi-stakeholder collaborative framework, encompassing local youth, NGOs, religious institutions, local government, and the customary council. The inaugural Egek Festival in 2023 exemplifies this collaboration, symbolizing the Moi tribe's commitment to sustainable resource management and cultural preservation. The research highlights the potential of integrating traditional ecological knowledge into modern conservation efforts and the importance of adapting global sustainability goals to local contexts. While the study's geographical scope and timeframe present limitations, its findings have significant implications for policy, practice, and future research in sustainable development, particularly in indigenous contexts. The Malaumkarta case offers valuable insights for achieving SDGs while preserving cultural heritage and ecological integrity, potentially informing similar initiatives worldwide